Analisis Implementasi Profil Pelajar Pancasila dalam Membentuk Karakter Siswa Kelas V SDN 2 Balerejo - Ahmad Izzul Ito; Arina Manasikana (International Forum of Researchers and Lecturers, 2024)
Education is a process of developing all aspects of human life including knowledge, skills and character values. Western paradigms that enter Indonesia need to be sorted out, especially cultural deviations and Pancasila values. Strengthening character education seeks to shape student character to integrate Pancasila values, in order to create a generation with character, nationalist spirit, and global competence. The independent curriculum aims to realize Pancasila students through the implementation of the Pancasila Student Profile which is divided into six dimensions, namely faith, devotion to God Almighty and noble character, critical thinking, global diversity, independence, creativity, and mutual cooperation. This research used a descriptive qualitative approach. Data collection was done through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of student character education at SDN 2 Balerejo was carried out through learning activities, extracurricular activities, habituation, and the Student Character Education Strengthening Project. Supporting factors include school commitment, parental support and active student participation. However, there are some obstacles such as the lack of literacy, students' interest and willingness, and the low role of parents. This study suggests increasing school program innovation, improving parental support, and optimizing the learning process. Thus, it is expected that the Pancasila Student Profile can effectively shape students' character in accordance with the values of Pancasila and can be actualized in daily activities.